Identification and energy calibration of hadronically decaying tau leptons with the ATLAS experiment in pp collisions at √s = 8 TeV - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Hanke, Paul; Jongmanns, Jan; Kluge, Eike-Erik; Kugel, Andreas; Lang, Valerie; et al. (The European physical journal. C, Particles and fields, 2015)
This paper describes the trigger and offline reconstruction, identification and energy calibration algorithms for hadronic decays of tau leptons employed for the data collected from pp collisions in 2012 with the ATLAS detector at the LHC center-of-mass energy s√=8 TeV. The performance of these algorithms is measured in most cases with Z decays to tau leptons using the full 2012 dataset, corresponding to an integrated luminosity of 20.3 fb−1. An uncertainty on the offline reconstructed tau energy scale of 2–4 %, depending on transverse energy and pseudorapidity, is achieved using two independent methods. The offline tau identification efficiency is measured with a precision of 2.5 % for hadronically decaying tau leptons with one associated track, and of 4 % for the case of three associated tracks, inclusive in pseudorapidity and for a visible transverse energy greater than 20 GeV. For hadronic tau lepton decays selected by offline algorithms, the tau trigger identification efficiency is measured with a precision of 2–8 %, depending on the transverse energy. The performance of the tau algorithms, both offline and at the trigger level, is found to be stable with respect to the number of concurrent proton–proton interactions and has supported a variety of physics results using hadronically decaying tau leptons at ATLAS.
*ATLAS Collaboration: G. Aad, C.F. Anders, V. Andrei, A. Baas, O. Brandt, J.I. Djuvsland, M. Dunford, P. Hanke, J. Jongmanns, E.-E. Kluge, A. Kugel, V. Lang, K. Meier, S. Schaetzel, V. Scharf, S. Schmitt, A. Schoening, H.-C. Schultz-Coulon, R. Stamen, M. Wessels [und 2869 weitere Personen]
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
Gesehen am 12.07.2021